2014
DOI: 10.1155/2014/316568
|View full text |Cite
|
Sign up to set email alerts
|

DEM Study of Wet Cohesive Particles in the Presence of Liquid Bridges in a Gas Fluidized Bed

Abstract: A modified discrete element method (DEM) was constructed by compositing an additional liquid-bridge module into the traditional soft-sphere interaction model. Simulations of particles with and without liquid bridges are conducted in a bubbling fluidized bed. The geometry of the simulated bed is the same as the one in Müller’s experiment (Müller et al., 2008). A comparison between the dry and the wet particular systems is carried out on the bubble behavior, the bed fluctuation, and the mixing process. The bubbl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…However, due to the computational cost for a large number of particles, the simulation of U mf was not directly compared with the experimental data. Instead, a pseudo‐2D bubbling fluidized bed was simulated with a focus on particle velocity distribution 8 and granular temperature 19 under different liquid loadings. The CFD–DEM method was also used to simulate lab‐scale spout fluidized beds with liquid injection as the fluidized particles are generally larger and then the particle number for CFD–DEM simulation is reduced remarkably 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…However, due to the computational cost for a large number of particles, the simulation of U mf was not directly compared with the experimental data. Instead, a pseudo‐2D bubbling fluidized bed was simulated with a focus on particle velocity distribution 8 and granular temperature 19 under different liquid loadings. The CFD–DEM method was also used to simulate lab‐scale spout fluidized beds with liquid injection as the fluidized particles are generally larger and then the particle number for CFD–DEM simulation is reduced remarkably 20,21 …”
Section: Introductionmentioning
confidence: 99%
“…For prediction of agglomeration in wet granulation systems, in addition to the pressure gradient force, drag force, gravitational force and contact force, liquid bridge forces also need to be accounted for. This was introduced by He et al 95 in their softsphere DEM method. The liquid bridge force is comprised of the capillary and viscous dissipation forces due to the liquid bridge between interacting particles.…”
Section: Methodsmentioning
confidence: 99%
“…This may be caused by the following reasons: (1) the model assumes that the particles are spherical, but the particles used in the experiment are not uniform in shape and have certain roughness; (2) the DEM method requires that the mesh size is several times larger than the particle diameter. The existence of coarse mesh may lead to the problem of wall shear effect and further affect the particle velocity . In fact, the phenomenon of overestimating particle velocity exists in many research results, ,, Kuwagi et al showed that the simulation results may be greater than 30–40% of the experimental results.…”
Section: Simulation Conditions and Model Validationmentioning
confidence: 99%